Case Study on Managing Urban Expansion in Tokyo - Okazawa, Yuko; Murakami, Nozomi (World Bank, Washington, DC, 2019)
Tokyo, with a population of 38 million (2017) has been the world’s largest mega city for the past sixty years in terms of economic scale and population agglomeration. Through Japan’s drastic economic and social changes, this enormous city has been performing a difficult balancing act of managing urban growth at the national, prefectural, and municipal levels.